Flexible Formation of Nanoparticles: Selectively Self-Assembling with Glycoclusters to Form Nano-Photosensitizers for Multipurpose Bioimaging and Photodynamic Therapy - Kai-Li He; Wen-Jia Li; Yu Hu; Lu-Lu Sun; Lei Dong; Jing Xing; Jin Gong; Xiaoming Gong; Hai-Hao Han (Molecules)
The smart construction of nano-photosensitizers (PSs) is significant for multipurpose applications, such as bioimaging, efficient photodynamic anti-tumor or anti-bacterial studies. This work reports a flexible self-assembling strategy for the construction of nano-PSs, in which PSs spontaneously form amorphous aggregates for killing bacteria, or self-assemble with tetraphenylethene (TPE) based glycoclusters (TPE-Glc4) to construct glyco-dots for cell imaging and photodynamic anti-tumor studies. Tricyanofuran (TCF) and TPE units were bridged with furan or thiophene moiety to construct two PSs (1 and 2) with NIR fluorescence in monomers, and a performance of the aggregation-induced generation of reactive oxygen species (AIG-ROS) in an aggregated state. Compared to the large amorphous aggregates (2-a), TPE-based glycoclusters encapsulated with PS form glyco-dots (2-Glc) that exhibit a smaller and more homogeneous hydrated size of approximately 40 nm, as well as enhanced water-solubility and biocompatibility. TPE-glycoclusters facilitate the cellular uptake of 2 into HepG2 cells, therefore enhancing the NIR fluorescence imaging signal and photodynamic therapy. Meanwhile, 2-a exhibits satisfied phototoxicity against Escherichia coli. This work highlights the flexible self-assembly of nano-PSs for multifunctional bioapplications.